Post-extraction vertical guided bone regeneration with a titanium-reinforced polytetrafluoroethylene membrane - Duque Uriostegui, Carla B.; Gallo, Pier Luigi (International Surgery Journal, 2025)
Tooth loss can lead to resorption of the alveolar bone, affecting soft tissue support and altering the facial profile. The long-term success of dental implants depends on adequate bone dimensions, so guided bone regeneration (GBR) is crucial to increase bone volume prior to implant placement. GBR is a technique that promotes new bone formation in bone defects to create adequate support for dental implants. It uses a combination of autologous bone and xenograft to optimize the graft’s osteogenic and osteoconductive properties. However, its main limitation is the bone’s maturation time, which is usually between 6 and 9 months. A 58-year-old patient with tooth loss due to severe bone destruction required GBR for dental implant placement. The combination of the physical barrier of d-PTFE (polytetrafluoroethylene) and the structural strength of titanium provides a favorable environment for bone regeneration, but it is crucial to consider the potential complications associated with these membranes, such as soft tissue injury and membrane exposure.